A new type battery management system for Li-ion cell packs. Issue 6 (3rd October 2017) - Fu, Lin; Zhu, Chenghua; Du, Tao
Abstract: Aim: Structured a new type battery management system. Methods: Mainly combined the analog front end IC of ml523x with ml610q488P to compose the core of the BMS.Results: The system performs an intelligent BMS and provides an intelligent battery pack.Conclusion: The system is more inexpensive than any other BMS and performances the same function as well as reliability.